Financial Performance Analysis Using Financial Ratios At PT Diamond Food Indonesia Tbk - Dewi Arum Lestari; Achmad Wicaksono; Ferdiana Tri Pramesari (International Economic and Finance Review, 2024)
The purpose of this research is to analyse the financial performance of PT Diamond Food Indonesia Tbk during the period from 2020 to 2022 using financial ratio analysis, including liquidity, solvency, profitability, and activity ratios. The method employed in this research is quantitative descriptive method with data collection conducted through documentation and literature study. The data analysed are derived from secondary data sources, namely the annual financial reports for the period 2020 to 2022 obtained from the official website of the Indonesia stock Exchange. The research findings indicate that the financial performance of PT Diamond Food Indonesia Tbk. is considered “Very Good” based on liquidity and solvency ratios. However, the company’s financial performance is deemed “Less Favourable” based on profitability and activity ratios.